2021
DOI: 10.1037/dev0001213
|View full text |Cite
|
Sign up to set email alerts
|

The development of metacognitive accuracy in working memory across childhood.

Abstract: Growth in working memory capacity, the number of items kept active in mind, is thought to be an important aspect of childhood cognitive development. Here, we focused on participants’ awareness of the contents of their working memory, or meta-working memory, which seems important because people can put cognitive abilities to best use only if they are aware of their limitations. In two experiments on the development of meta-working memory in children between 6 and 13 years old and adults, participants were to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 114 publications
2
19
1
Order By: Relevance
“…Metacognitive skills are fundamental to promote the individual’s cognitive development, both in general (e.g. 48 , 49 , 55 ) and specifically in relation to STM/working memory development 53 , 54 . For instance, Forsberg and colleagues 54 compared meta-working memory judgments to actual performance in children between 6 and 13 y.o.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Metacognitive skills are fundamental to promote the individual’s cognitive development, both in general (e.g. 48 , 49 , 55 ) and specifically in relation to STM/working memory development 53 , 54 . For instance, Forsberg and colleagues 54 compared meta-working memory judgments to actual performance in children between 6 and 13 y.o.…”
Section: Discussionmentioning
confidence: 99%
“… 48 , 49 , 55 ) and specifically in relation to STM/working memory development 53 , 54 . For instance, Forsberg and colleagues 54 compared meta-working memory judgments to actual performance in children between 6 and 13 y.o. and adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically on the relation of metacognition and working memory, Forsberg et al (2021) showed that younger children poorly estimate their working memory performance, although they become increasingly better at doing it with age. In this study, these authors asked typically developing children of different ages (9 to 13) and adults to judge their own accuracy in a working memory recognition test (i.e., memorize an array of objects and recognize a probe item as part of the array).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%